Mechanism Study on the Axial Compressive Performance of Short Square CFST Columns with Different Stiffeners - Bing Xu; Fahong Wu; Guizhong Xu (Advances in Civil Engineering)
In order to limit the disengaging of short square concrete-filled steel tube (CFST) columns and strengthen the combined action of steel tubes and concrete, a reinforcing method of stiffener is put forward in this paper. The axial compression performance and mechanism are studied through experiments, which indicate that (1) the buckling model of stiffening members changes into double wave, (2) stiffeners enforce the constraint in core concrete, (3) stiffeners can effectively improve the ultimate bearing capacity, (4) the stiffeners increase the stress in the middle of the steel tube and improve the distribution of stress for the core concrete, and (5) the direct ribs have more influence on the bearing capacity while ribs with holes have more impact on the deformation of the tube. At the end of the article, a formula for calculating the ultimate bearing capacity is presented, which can bring out a more accurate bearing capacity value.